Application of the Modified Вagolini Test in the Diagnosis of Binocular Vision Disorders - S. I. Rychkova; V. G. Likhvantseva (Oftalʹmologiâ)
The work is devoted to one of the most actual problems of current strabismology — the development of effective ways to study binocular vision.The purpose — to study the effectiveness of the developed modification of the Bagolini test in the diagnostics of binocular disorders.Patients and methods. 240 patients with non-paralytic strabismus aged from 6 to 17 (on average 10.8 ± 0.24) years were observed. There were 190 patients with converging strabismus and 50 patients with diverging strabismus. The control group consisted of 180 children aged also from 6 to 17 (on average 10.9 ± 0.3) years without ophthalmopathology. All children were examined for the character of vision using a Worth-test, the classic Bagolini test (CTB), and the developed modified Bagolini test (MTB). If the patient has a strabismus angle, the study was performed in two variants: without prismatic deviation compensation (under the subjective angle of strabismus — SU) and under full prismatic compensation (under the objective angle of strabismus — OU). For qualitative assessment of binocular vision with MTB, static presentation of the test image was used, for quantitative assessment — alternating (alternate presentation of details corresponding to the right and left eyes).Results. The qualitative evaluation data obtained with the help of MTB made it possible to differentiate patients with non-permanent regional functional scotoma of suppression (FSP) and patients with stable bifoveal fusion among children with binocular vision by color test, and to distinguish patients with regional stable FSP and total FSP among children with monocular vision by color test. In the study under SU, the sensitivity of the method was 97.8 % and specificity 96.2 %, under OU — 96.6 % and 92.7 %, correspondingly. Using quantitative evaluation, it was found that the minimum duration of monocular phases required to eliminate functional inhibition in children with total FSP is twice as long as in children with regional FSP (z = 6,303, df 52, p < 0.001 according to the Mann — Whitney criterion).Conclusion. Thus, the modified Bagolini test developed by us is an effective way of qualitative and quantitative assessment of the state of binocular vision. The method has a high sensitivity and specificity, combines the capabilities of anaglyphic and phase haploscopy, and can be used for a personalized approach to the selection of conditions and modes of functional correction of binocular disorders, as well as for monitoring binocular vision during treatment.